2013
DOI: 10.1007/s00339-013-7737-9
|View full text |Cite
|
Sign up to set email alerts
|

Negative differential resistance in ZnO coated peptide nanotube

Abstract: We investigate the room temperature electronic transport properties of a zinc oxide (ZnO) coated peptide nanotube contacted with Au electrodes. Current–voltage (I–V ) characteristics show asymmetric negative differential resistance (NDR) behavior along with current rectification. The NDR phenomenon is observed in both negative and positive voltage sweep scans, and found to be dependent on the scan rate and humidity. Our results suggest that the NDR is due to protonic conduction arising from water molecule redo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…In the previous studies, the ambient conditions have found to influence the charge transport mechanisms through electrochemical reactions in the ambient environment and similar NDR peaks have been observed in I-V characteristics of ZnO coated peptide nanotubes and DNA thin films where it is activated by the dissociation of water molecules. (when the applied electric field reaches its electrochemical redox potential) 44 , 45 . In these studies, the NDR peak in electrical conductivity is attributed to protonic (H + ions) conduction which is based on electrolysis of adsorbed water (Grotthuss mechanism) at the electrodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the previous studies, the ambient conditions have found to influence the charge transport mechanisms through electrochemical reactions in the ambient environment and similar NDR peaks have been observed in I-V characteristics of ZnO coated peptide nanotubes and DNA thin films where it is activated by the dissociation of water molecules. (when the applied electric field reaches its electrochemical redox potential) 44 , 45 . In these studies, the NDR peak in electrical conductivity is attributed to protonic (H + ions) conduction which is based on electrolysis of adsorbed water (Grotthuss mechanism) at the electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…4(a) . This rapid increase in the channel current is swiftly limited by the depletion and slow diffusion of the thin adsorbed layer of water on the GO channel, thus resulting in the NDR peak 44 , 49 . Unlike in the previous studies, where repeated observation of NDR was missing due to the limited rate of water diffusion, GO device do not show such relaxation and NDR can be observed in subsequent sweeps as well.…”
Section: Resultsmentioning
confidence: 99%
“…Some theories associated with defects (e.g. grain boundary, dislocation, and vacancy) have been proposed; these theories include the resonant tunneling conduction of charges, 13 the current in oxygen vacancy migration, etc. 7 These results show that the emergence of NDR in TMOs and its mechanism of action are closely related to the microscopic structures of TMOs themselves.…”
Section: Introductionmentioning
confidence: 99%
“…В случае окислительно-восстановительного механизма ОДП происходит за счет окисления и восстановления активных молекул при определенном напряжении [17]. Происхождение ОДП в структурах Al/OH−La 2 O 3 /p-Si можно объяснить протонной проводимостью, возникающей в результате диссоциации воды (H 2 O ↔ H + + OH − ) на поверхности пленки.…”
unclassified